Pengaruh Pemberian CaCI2 Prapanen terhadap Perubahan Kualitas Tomat Segar Selama Penyimpanan - Fitri Normasari; Bambang S . Purwoko (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2002)
The objective of the research was to determine the effect of pre harvest CaCI2 application on quality changes of tomato fruits. Experiment consisted of 5 treatments: control, application of 0.1 M CaCI2 at 18 ± 2 days after anthesis (DAA), 0.1 M CaCI2 at 25 ± 2 DAA, 0.2 M CaCI2 at 18.t2 DAA and 0:2 M CaCI2 at 25 ± 2 DAA. Tomato fruits cv. Ratna harvested at breaker stage were used throughout the experiment. Variables to be observed were peel color, weight loss, fruit firmness. total soluble solids, titratable acidity, and respiration. Result of the experiment showed that application , of CaCl2 could not maintain quality and extend shelf life. Application of 0.1 M CaCl2 at 25 ± 2 DAA inhibited peel color. development at  9. 12, and 21 days after harvest.   Key words: Pre harvest, CaCI2, Tomato, Storage